Peeking through the other’s deja vu Maria Clara at Ibarra as a mnemonic device for remembering the past and understanding the Filipino identity - Chomi, Samantha Santos
By depicting the lives of the Filipino under the Spanish colonial rule, Rizal and his novels Noli Me Tangere and El Filibusterismo played a huge role in the independence that the nation enjoys today. Even after a century, his works are deemed important in instilling nationalism among Filipinos, especially the youth. However, many scholars have noted that because of the education crisis in our country, where history is taught and learned without being critical of the consequences of colonialism, Filipinos forget their past and remain in the shadow of their colonizers identities.